(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Obesity is rapidly escalating worldwide in all age groups. Childhood obesity is associated with a greater long-term risk of hypertension and type 2 diabetes mellitus in adulthood. Objectives: To observe the relationship of peak expiratory flow rate (PEFR) with obesity. Methods: Two hundred students were selected from two different schools of Narayanganj city by following inclusion criteria- for group A: BMI of > 95th percentile for age and sex was taken as obese and for group B: BMI of 10th- 85th percentile for age and sex was taken as non-obese. The anthropometric measurements and PEFR were measured by standard procedure. Results: PEFR were found statistically significant in non-obese than obese groups (p<0.05) in the following variables-height, weight, BMI and age. The stronger correlation was with BMI, weight and height (P < 0.001) and lesser correlation was with age (<0.05) Conclusion: This study PEFR significant positive correlation with non-obese than obese children. Bangladesh J Child Health 2015; VOL 39 (2) :77-81